Predictors of relapse or maintenance of response in pediatric and adult patients with attention-deficit/hyperactivity disorder following discontinuation of long-term treatment with atomoxetine - Thome, Johannes; Dittmann, Ralf (ADHD Attention Deficit and Hyperactivity Disorders, 2017)
We identified relapse/maintenance-of-response (MOR) predictors following discontinuation of long-term atomoxetine treatment in pediatric and adult patients with attention-deficit/hyperactivity disorder (ADHD) and assessed correlations between ADHD symptoms and quality of life (QoL). Post hoc analyses of data from two randomized, double-blind, placebo-controlled, phase 3 withdrawal studies in patients with ADHD meeting predefined response criteria before randomization. Study 1: patients (N = 163; 6-15 years) received atomoxetine (1.2-1.8 mg/kg/day) for 1 year, followed by randomization to atomoxetine (n = 81) or placebo (n = 82) for 6 months. Study 2: patients (N = 524; 18-50 years) received atomoxetine (80-100 mg/day) for ~6 months, followed by randomization to atomoxetine (n = 266) or placebo (n = 258) for ~6 months. Placebo patients were used for the analyses. Relapse: ≥50% worsening of prerandomization improvement in ADHD symptoms and ≥2 level severity increase on the Clinical Global Impression-Severity (CGI-S) scale at 2 consecutive visits; MOR: retaining ≥75% of prerandomization symptom improvement and CGI-S ≤ 2 at all visits (study 1); retaining ≥70% of prerandomization symptom improvement and CGI-S ≤ 3 at all visits (study 2). In adults, statistically significantly (P ≤ .05) increased likelihood of relapse was associated with prerandomization presence of Conners’ Adult Attention-Deficit/Hyperactivity Disorder Rating Scale-Investigator-Rated:Screening Version (CAARS-Inv:SV) items “difficulty awaiting turn” and “careless mistakes.” In pediatric patients, less MOR was associated with prerandomization presence of ADHD Rating Scale-IV-Parent Version Investigator-Rated item “does not listen”; in adults, less MOR was associated with prerandomization presence of CAARS-Inv:SV items “loses things” and “difficulty awaiting turn.” Changes in patients’ QoL after withdrawal from atomoxetine moderately correlated with changes in ADHD symptoms in pediatric patients and mildly in adults.
Gesehen am 03.05.2018